Optimal Allocation of Water Resources Based on GWAS Model in Handan,China - LIU Guanghui; SUN Jianwei; LUO Yun; ZHAO Xian; REN Shuai; LIU Ruiting; WANG Jixuan (Renmin Zhujiang)
In recent years,the inflow of upstream rivers in Handan City has decreased,and the total amount of groundwater exploitation has become more limited,which fails to meet the rising water demand of different industries.In addition,due to the replacement of water supply sources for some industries after the construction of the South-to-North Water Diversion Project,the Yellow River Diversion Project,and the Yinwei River Water Diversion Project,the shortage and the contradiction between supply and demand of water resources in Handan City are becoming acute and complex.By analyzing the characteristics of water resources and the distribution characteristics of water conservancy projects in Handan City,the water supply and demand of each district and county in Handan City are predicted,and a multi-source,multi-user,and multi-objective optimal allocation model of water resources in Handan City is constructed based on GWAS.The results show that the total water demand in Handan City with a guarantee rate of P=50% in 2025 is 3 013.01×106 m3;the total water allocation is 2 473.97×106 m3,and the water shortage rate is 17.89%.The total water demand with a guarantee rate of P=75% is 3 434.90×106 m3;the total water distribution is 2 498.22×106 m3,and the water shortage rate is 27.27%.The water shortage is mainly concentrated in the primary industry.The allocation results are in line with the actual water consumption situation in Handan City,and the research results can provide a technical reference for water resources management in Handan City.